Analysis of design criteria in sewerage system at Taman Mahkota Aman, Pahang - Nur Ratna Shahirah, Yahya (2018)
Reliable estimation of sewage flow rates is essential for the proper design of sewers, pumping stations, and treatment plants. Poor analysis of the flow design parameters might influence the capacity of a sewerage system, initiating health and environmental problems. The aim of this study is to determine the design criteria of the sewerage system in Taman Mahkota Aman at Kuantan, Pahang. Malaysian Sewerage Industry Guidelines (MSIG) is the local practice of sewerage system in Malaysia. The flow design parameters in MSIG are taken from Malaysian Standard Code of Practice for Design and Installation of Sewerage System (MS1228:1991). A manhole in the sewerage treatment plant was selected to carry out this study. The data was collected every five minutes for 24 hours every day including weekdays and weekends. The data was collected from 25/8/2017 until 29/1/2018. The equipment used to collect the data was the ISCO 2150 Area Velocity Flow Meter. The flow parameters which are the actual per capita flow and the actual design criterion were calculated using equations once flow rates collected were analyzed. The results of this research show that the values of per capita flow are higher than the value recommended in MS 1228:1991. The average per capita flow during the period of study was calculated to be 0.373